Changes and effects of the Syrian civil war on the Syrian-American diaspora. (c2017) - Bissar, Racha El (2017)
The Syrian conflict, which originated as a rebellion against the regime and descended into civil war has had grave repercussions and has affected people in a wide geographical area. It has also had its impact on the Syrian Diaspora across the world to varying degrees. This thesis studies the effects of the war on the intra-group dynamics and the relations with the host society of the Syrian-American community of New Jersey. The research examines the ethnic organizations of this community and unearths, by studying the work of the associations, the changes that have taken place in intra-group dynamics and in the relations of the group with the New Jersian society. The diaspora in New Jersey has been politicized, experienced renewed group consciousness and displayed high levels of tension. Conversely, its relations with the New Jersian society have been improved by the crisis. This thesis offers insights into what the Syrian-American communities may be experiencing across other states and factors to be explored in other countries with a large Syrian diaspora. The research falls into fields of study of diaspora politicization and identity activation following a stimulus such as a war in the homeland.